Development and validation of different spectrophotometric and chromatographic methods for determination of clotrimazole and hydrocortisone in a topical cream - Fares, Michel Yousry; Abdelrahman, Maha Mohamed; Abdel-Rahman, Hamdy Mohamed; Abdelwahab, Nada Sayed (European Journal of Chemistry, 2017)
In this study, we developed and validated different spectrophotometric and chromatographic methods for determination of clotrimazole (CLO) and hydrocortisone (HDC) in their combined dosage form. The developed spectrophotometric methods were first derivative spectrophotometry (1D) by measuring the peak amplitude at 247.4 and 236.2 nm for CLO and HDC, respectively, second derivative of ratio spectra (2DD) at 225.4 nm for CLO and 269 nm for HDC, dual wavelength spectrophotometry (DW) by measuring absorbance difference between 225.4 and 264 nm for CLO and between 228 and 247 nm for HDC determination, advanced absorbance subtraction method (AAS) between 225.4 and 264 nm and mean centering of ratio spectra (MCR) spectrophotometric method in the range of 232-265 nm. On the other hand, the proposed chromatographic method was Ultra Performance Liquid Chromatography method (UPLC) using acetonitrile:water (50:50, v:v) as a mobile phase and the peaks were detected at 228 nm. All these methods were successfully applied to determine the two studied drugs in pure forms; laboratory prepared mixtures and combined dosage form. Methods validations were carried out regarding linearity, accuracy, precision and selectivity. The spectrophotometric methods exhibited a linear dynamic range over 5-40 and 5-45 µg/mL for CLO and HDC, respectively, and over 3-35 and 5-50 µg/mL for UPLC method. Sensitive and selective spectrophotometric and UPLC methods for the determination of clotrimazole and hydrocortisone in their topical formulation were successfully developed and validated. The developed methods were statistically confirmed to be accurate, precise and reproducible.